2002
DOI: 10.1149/1.1490358
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Cyanoacetic Acid from Chloroacetonitrile and Carbon Dioxide

Abstract: The electrochemical carboxylation of chloroacetonitrile was investigated in dimethylformamide ͑DMF͒ and acetonitrile ͑MeCN͒ by cyclic voltammetry and controlled-potential electrolysis. Both direct electroreduction and mediated reduction of the halide in CO 2 -saturated solvents were used to achieve the electrocarboxylation process. Also the effects of cathode material and cell type ͑divided or undivided with dissolving anode͒ were examined. In DMF the electrolyses performed in the divided cell resulted in low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…Further improvements in the electrocarboxylation processes employing redox mediators [3][4][5] and silver cathodes [6,7] have been reported. Poly halogenated aromatic compounds [8], iodo aromatic compounds [9] and aliphatic halides [10,11] also undergo facile electrocarboxylation. Al 3?…”
Section: Introductionmentioning
confidence: 99%
“…Further improvements in the electrocarboxylation processes employing redox mediators [3][4][5] and silver cathodes [6,7] have been reported. Poly halogenated aromatic compounds [8], iodo aromatic compounds [9] and aliphatic halides [10,11] also undergo facile electrocarboxylation. Al 3?…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have previously demonstrated that the selectivity of the process at carbon cathodes depends essentially on the competition between these reactions [8,9]. • All homogeneous reactions take place within a thin strip of solution (denoted "reaction layer") adjacent to the electrode, whose thickness is vanishing small as compared to that of the diffusion layer, ı, whose size is fixed by the cell hydrodynamics.…”
Section: Theoretical Considerations On Preparative Electrolysismentioning
confidence: 99%
“…The use of dangerous reagents such as cyanides makes this method of preparation an environmentally unfriendly process. For this reason, important research efforts have been carried out in the last 2 decades to find alternative methods using less dangerous reagents [2][3][4][5][6][7][8][9]. In particular, two electrochemical methods have recently been developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations